STIMULASI PERTUMBUHAN DAN PERKEMBANGAN PLANLET ANGGREK (Dendrobium sp) PADA TAHAP AKLIMATISASI DENGAN PEMBERIAN VITAMIN B1 DAN ATONIK - Riski Abdul Latif; Syahbudin Hasibuan; Siti Mardiana (Universitas Medan Area, 2020)
Dendrobium sp is a type of orchid that is currently very popularly traded because it has a variety of flower types, but the growth rate is slow. Vitamin B1 (Thiamin) is a micro nutrient that is able to accelerate the division of new cells in the tissue so that it can accelerate the growth of plant vegetative organs. Atonic is a chemical that can stimulate the biochemical and physiological processes of plants, so that atonics is a growth regulator. Atonic is usually used to stimulate the growth of plant roots against nutrients, increase leaf absorption, flower discharge, fruit formation, and increase the number and weight of fruit. The purpose of this study is the Stimulation of Growth and Development of Planlet Orchid (Dendrobium sp) in the Acclimatization Stage by Provision of Vitamin B1 and Atonik.This research was conducted experimentally using a completely randomized design (CRD) with 2 factors, namely the concentration of Vitamin B1 (Thiamin) consisting of 4 treatment groups and Atonic consisting of 4 treatments. Vitamin B1 (0 ml / l, 1.5 ml / l, 3 ml / l, 4.5 ml / l) and Atonik (0 ml / l, 1 ml / l, 2 ml / l, 3 ml / l) and each treatment was repeated 2 times so that 128 plants could each treatment consisting of 4 plants with 4 sample plants. Spraying is done once a week. The parameters observed were percentage growth, plant height, stem diameter, number of leaves, primary root length and number of roots and measured at 2MST.Based on the results of research on Dendrobium sp. Can be concluded 1) Provision of Vitamin B1 significantly affect the growth of orchid plant height (Dendrobium sp). 2) The giving of Atonik significantly influences the growth of the number of leaves, root length and number of roots of orchid plants (Dendrobium sp). 3) Provision of Vitamin B1 and Atonik simultaneously can accelerate to overcome plant height, number of leaves and the budding of orchid plant roots (Dendrobium sp).